IMPLEMENTATION OF THE FREEDOM TO LEARN CURRICULUM IN ENHANCING STUDENTS' LEARNING CREATIVITY - Fikri, Sadid (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The aim of this research is to determine the application of the Independent Learning Curriculum in Islamic Religious Education at MTs AL Muttahidah Sentong and to determine the effectiveness of the Independent Learning Curriculum in increasing students' learning creativity in Islamic Religious Education learning at MTs AL Muttahidah Sentong. This type of research is descriptive qualitative research, namely research that provides a description of factual and systematic situations and events regarding the factors, characteristics and relationships between phenomena in order to understand only the basics. The subjects in this research were all Class IX MTs students. Al Muttahidah Sentong semester 2 of the 2023/2024 academic year, totaling 25 students. The data obtained in this research include: learning outcomes and student learning completion taken from giving test questions at the end of each meeting and students' activeness in the learning process. From this research, it can be concluded that students' learning creativity in Islamic Religious Education learning at MTs. Al Muttahidah Sentong experienced improvement after implementing learning by implementing the independent curriculum as an embodiment of the concept of independent learning.